UPAYA MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS MELALUI PENDEKATAN REALISTIC MATHEMATICS EDUCATION - Chelvy Yoelanda; Maimunah; Nahor Murani Hutapea (Jurnal Ilmiah Matematika Realistik, 2026)
This classroom action research aimed to improve the instructional process and enhance students' mathematical understanding ability through the application of the Realistic Mathematics Education (RME) approach in class XI TKJ 2 of SMK Negeri 1 Pekanbaru. A collaborative classroom action research design was used, conducted over two cycles, each consisting of planning, action, observation, and reflection. The study was carried out in the odd semester of the 2025/2026 academic year on the topics of composite functions, inverse functions, and function transformations. Data were collected through a mathematical understanding test in the form of essay questions and observation sheets documenting teacher and student activities throughout the learning process. The data were analyzed using descriptive and qualitative techniques. The results show that the implementation of the RME approach improved the learning process and increased students' mathematical understanding ability. The improvement in the learning process was indicated by the increasing quality of instruction in line with the stages of the RME approach, as reflected in the observations of teacher and student activities. In addition, the mathematical understanding test results demonstrated a gradual increase between before and after the intervention. This was evidenced by the rise in the number of students in the very high category from 2 to 12, accompanied by a decrease in those in the very low category from 19 to 4. Based on these findings, the RME approach is proven capable of improving the instructional process and enhancing the mathematical understanding ability of class XI TKJ 2 students at SMK Negeri 1 Pekanbaru in the odd semester of the 2025/2026 academic year on the topics of composite functions, inverse functions, and function transformations.